KASIH DAN KUASA DITINJAU DARI PERSPEKTIF ETIKA KRISTEN - Rencan Carisma Marbun (Institut Agama Kristen Negeri Tarutung, 2019)
AbstractOur understanding of “Love and Power” at a glance seems to be the opposite of one another. Generally, the term “Love” is related to understanding or elements that are always modest, succumbing, helpfull, gentle, doing good or in other words always related to conscience “Love” is done not with the intention of being rewarded, but sincerely done and selflessly. Likewise about the term “Power”, it seems like the opposite of “Love”, as if “Power is something that relies on authoritarianism, governing, regulating without compromise, and found in a system of royal government that has the right or authoritarian to regulate the one under it based on the power that is in it. In this paper, the writer tries to describe the meaning and reciprocity of the two words which are viewed in term of Christianity in terms of Christianity, “Love and Power” is not two words that have conflicting meanings, but are interconnected and influence each other in realizing a complete system or link. So in Christianity, the understanding of “Love and Power” is not acontradiction.Keywords: “Love and Power”